2014
DOI: 10.1093/nar/gku1296
|View full text |Cite
|
Sign up to set email alerts
|

A new heavy lanthanide-dependent DNAzyme displaying strong metal cooperativity and unrescuable phosphorothioate effect

Abstract: In vitro selection of RNA-cleaving DNAzymes was performed using three heavy lanthanide ions (Ln3+): Ho3+, Er3+ and Tm3+. The resulting sequences were aligned together and about half of the library contained a new family of DNAzyme. These DNAzymes have a simple loop structure, and they are active only with the seven heavy Ln3+. Among the tested non-lanthanide ions, only Y3+ induced cleavage and even Pb2+ failed to cleave, suggesting a very high specificity. A representative DNAzyme, Tm7, has a sigmoidal metal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(122 citation statements)
references
References 53 publications
8
114
0
Order By: Relevance
“…42 We recently reported that the Tm7 DNAzyme employs three Ln 3+ ions cooperatively. 30 In this study, Dy10a employs two Ln 3+ ions, further supporting the assertion that it is a new DNAzyme. Dy10a is also a very efficient enzyme; its rate reaches ~0.7 min -1 with 0.5 µM Sm 3+ , the highest among all reported Ln 3+ -dependent DNAzymes at pH 6.…”
Section: Dy10a Is Highly Specific For Lnsupporting
confidence: 70%
See 4 more Smart Citations
“…42 We recently reported that the Tm7 DNAzyme employs three Ln 3+ ions cooperatively. 30 In this study, Dy10a employs two Ln 3+ ions, further supporting the assertion that it is a new DNAzyme. Dy10a is also a very efficient enzyme; its rate reaches ~0.7 min -1 with 0.5 µM Sm 3+ , the highest among all reported Ln 3+ -dependent DNAzymes at pH 6.…”
Section: Dy10a Is Highly Specific For Lnsupporting
confidence: 70%
“…Tm7 is nearly inactive with the first seven light Ln 3+ but is highly active with the heavy ones. 30 Tm7 binds three Ln 3+ ions cooperatively, which has never been observed previously for DNAzymes.…”
supporting
confidence: 58%
See 3 more Smart Citations